A Broken Engagement: Reassessing Barth's Relationship to Kierkegaard on the Grounds of Subjectivity and Preaching. (January 2014) - Edwards, Aaron
Abstract Despite Barth's initial appropriations of Kierkegaard, he famously discarded the Dane from the theological 'canon' due to the latter's alleged anthropocentric subjectivism. Yet Kierkegaard was himself a preacher and polemical homiletician, seeking merely to appropriate the objective truth of the proclaimed word. Barth's Basel prison sermons reveal this same endeavour to render the eternally significant message temporally significant for his hearers. In Kierkegaard's Christendom, a corrective focus on subjectivity was the only way to remain faithful to the 'objective' truth of the gospel. Barth and Kierkegaard are juxtaposed here not in contrast (as Barth might have preferred) but in affinity, in that both sought to evoke the dialectical subjectivity of objectivity through preaching.